2015
DOI: 10.1016/j.actamat.2015.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, chemistry and mechanical properties of Ni-based superalloy Rene N4 under irradiation at room temperature

Abstract: a b s t r a c tNickel superalloys with cubic L1 2 structured c 0 (Ni 3 (Al, Ti)) precipitates exhibit high strength at high temperatures and excellent corrosion resistance when exposed to water. Unlike prior studies on irradiation damage of other Ni-based superalloys, our study on Rene N4 involves much larger c 0 precipitates, $450 nm in size, a size regime where the irradiation-induced disordering and dissolution kinetics and the corresponding mechanical property evolution are unknown. We report that under he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Despite the fact bulk equiatomic FeCo magnetic alloys were firstly synthesized around 1920s [72][73][74], this present work demonstrated that FeCo nanomagnets can be easily synthesized via thermal annealing at relatively intermediate temperatures (773 K) starting with a nanocrystalline CoCrCuFeNi HCA (as-deposited) and, more important, they remain thermodynamically stable at room temperature (which is a challenge to achieve on nanoscale magnetic materials field [75]). Another experimental observation is that the FeCo nanomagnets appear not to be stable under heavy ion irradiation, undergoing ballisticassisted dissolution and mixing [76,77]; however, they can be restored upon annealing after irradiation which suggests they are highly stable.…”
Section: Formation Of Magnetic Feco Nanoprecipitates and Technologicamentioning
confidence: 99%
“…Despite the fact bulk equiatomic FeCo magnetic alloys were firstly synthesized around 1920s [72][73][74], this present work demonstrated that FeCo nanomagnets can be easily synthesized via thermal annealing at relatively intermediate temperatures (773 K) starting with a nanocrystalline CoCrCuFeNi HCA (as-deposited) and, more important, they remain thermodynamically stable at room temperature (which is a challenge to achieve on nanoscale magnetic materials field [75]). Another experimental observation is that the FeCo nanomagnets appear not to be stable under heavy ion irradiation, undergoing ballisticassisted dissolution and mixing [76,77]; however, they can be restored upon annealing after irradiation which suggests they are highly stable.…”
Section: Formation Of Magnetic Feco Nanoprecipitates and Technologicamentioning
confidence: 99%
“…In order to develop more efficient advanced solidification technology, a data base of superalloys on thermophysical properties is increasingly needed [3]. From a theoretical and industrial perspective, knowledge of superalloy solidification behavior is crucial for the controlling of the superalloy casting process [4]. In the casting of nickel-based superalloys, the mechanical properties of alloys are due to microstructure characteristics, such as a combined matrix γ phase and γ′ precipitation phase [5], dendritic width [6] and grain size [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop more efficient advanced solidification technology, the data of superalloys on thermophysical properties are increasingly needed [3]. From a theoretical and industrial perspective, knowledge of superalloy solidification behavior is crucial for the controlling of superalloy casting process [4]. For the nickel based superalloys, the matrix of alloy named gamma phase (γ) and the precipitate phase is known as gamma prime phase (γ′).…”
Section: Introductionmentioning
confidence: 99%